2023
DOI: 10.1097/dss.0000000000003931
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Prevention of Hemorrhagic Complications Following Interpolated Flap Repair: A Single-Center, Retrospective, Cohort Study

S. Caleb Freeman,
Michael S. Heath,
Brett Neill
et al.

Abstract: BACKGROUND Tranexamic acid (TXA) is increasingly being used to prevent hemorrhagic complications after dermatologic surgery. Interpolated flap repairs following Mohs micrographic surgery are at risk for increased bleeding events and unplanned health care utilization, particularly among patients on antithrombotic medication. OBJECTIVE To assess bleeding events after interpolated flap repair in patients receiving TXA compared with those who did not. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Subcutaneous TXA may also reduce bleeding complications in high-risk patients undergoing interpolated flap reconstruction for nasal defects after MMS. 5 This case report highlights the potential perioperative complications while on ruxolitinib. As the indications for JAK inhibitors increase, surgeons should exercise caution until the current preoperative guidelines are optimized.…”
Section: Author Contributionsmentioning
confidence: 86%
See 1 more Smart Citation
“…Subcutaneous TXA may also reduce bleeding complications in high-risk patients undergoing interpolated flap reconstruction for nasal defects after MMS. 5 This case report highlights the potential perioperative complications while on ruxolitinib. As the indications for JAK inhibitors increase, surgeons should exercise caution until the current preoperative guidelines are optimized.…”
Section: Author Contributionsmentioning
confidence: 86%
“…Theoretically, TXA may increase the risk of thrombosis, though studies have not demonstrated an increase in thrombotic events 4 . Subcutaneous TXA may also reduce bleeding complications in high‐risk patients undergoing interpolated flap reconstruction for nasal defects after MMS 5 …”
Section: Discussionmentioning
confidence: 99%